2020
DOI: 10.3389/fphar.2020.503524
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavonoids of Rhizoma Drynariae Enhances Angiogenic-Osteogenic Coupling During Distraction Osteogenesis by Promoting Type H Vessel Formation Through PDGF-BB/PDGFR-β Instead of HIF-1α/ VEGF Axis

Abstract: Background: Total flavonoids of Rhizoma Drynariae (TFRD), extracted from the kidney-tonifying traditional Chinese medicine Rhizoma Rrynariae, has been proved to be effective in treating osteoporosis, bone fractures and defects. However, pharmacological effects of TFRD on type H vessels, angiogenic-osteogenic coupling in distraction osteogenesis (DO) and the mechanism remain unclear. This study aims at investigating whether type H vessels exist in the DO model, effects of TFRD on angiogenic-osteogenic coupling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
3
24
1
1
Order By: Relevance
“…In the range of dose and time of our study, TFRD was relatively safe for non-cancer rats. According to the current reports, after TFRD acted on the rat models of bone defect, fracture, osteoporosis and osteonecrosis of femoral head, no carcinogenic and other adverse reactions were found (Song et al, 2016;Song et al, 2017;Yao et al, 2018;Guo et al, 2019;Shen et al, 2020;Lv et al, 2021). The doses of administration in these articles can be summarized as 75-440 mg/kg/d (oral administration) and 20 mg/kg/day (intraperitoneal injection), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…In the range of dose and time of our study, TFRD was relatively safe for non-cancer rats. According to the current reports, after TFRD acted on the rat models of bone defect, fracture, osteoporosis and osteonecrosis of femoral head, no carcinogenic and other adverse reactions were found (Song et al, 2016;Song et al, 2017;Yao et al, 2018;Guo et al, 2019;Shen et al, 2020;Lv et al, 2021). The doses of administration in these articles can be summarized as 75-440 mg/kg/d (oral administration) and 20 mg/kg/day (intraperitoneal injection), respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that when E2 binds to ERα, SRC forms the complex, SHP2-c-Src, in a non-genomic manner which weakens RANKL stimulation-induced c-Src activation, resulting in impaired actin ring formation and reduced bone reabsorption (27). At the same time, Src was also considered as one of the important protein targets of Rhizoma Drynariae in a network pharmacological study of Rhizoma Drynariae, a traditional Chinese medicine with anti-inflammatory and anti-oxidative effects on bone (28)(29)(30)(31). To conclude, through combining bioinformatic analysis with gene expression and microarray analysis, our study has discovered the abnormal expression of genes and pathways in patients of postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that RD could enhance angiogenic-osteogenic coupling during distraction osteogenesis by promoting type H vessel formation through PDGF-BB/PDGFR-β signaling pathway 14 . RD could promote osteoblast differentiation and mineralization in MC3T3-E1 cells through regulation of bone morphogenetic protein-2, alkaline phosphatase, type I collagen and collagenase-1 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Rhizoma Drynariae (RD), the dried rhizome of Drynaria fortune (Kunze) J. Sm., has been widespread and been proved to be effective in treating OP, bone fractures and defects [11][12][13][14][15][16] . Due to the minimum side effects and favorable cost-effective therapeutic effects, RD has been widely used in clinical practices for more than 2,100 years in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation